Serviço de referência na Biblioteca Pública do Amazonas: competências do bibliotecário no atendimento ao usuário surdo - Nunes, Gabriella Coelho (Brasil, 2022)
This study presents the investigation of the necessary competencies for the reference and information service librarian (RIS) performance in serving deaf users. The specific objectives of this study sought to identify in the literature the knowledge, skills and attitudes of the librarian, to verify which competencies are necessary to serve deaf users, and to map the practice of the reference service of the Public Library of Amazonas about what types of competencies librarians have. Then, this research sought to verify the validation of the found competencies with experts and finally, to present a map of competencies that highlights the knowledge, skills and attitudes to work in the reference service. This is a case study with a qualitative approach and applied nature, because in addition to using the literature review to support this study, it also aims to identify the skills of librarians in assisting deaf users in the practice of reference service, and as a method and technique of data collection, it was used the interview with the professional who works in the reference sector of the Public Library of Amazonas, which was validated through an interview protocol. In relation to the competencies identified in the literature and validated by the specialist, knowing how to communicate in LIBRAS, identifying the user profile and providing resources for accessibility in the services, products and materials of the collection were the skills that stood out. From the information obtained, it was concluded that the skills found in the literature are far from the practice in the reference service of the Amazon Public Library. It was identified that the librarian does not know sign language, as well as, there is no training to prepare the team to receive deaf users, and few materials in the collection are accessible.